(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2019)
In Trickster Chases the Tale of Education, teacher and scholar Sylvia Moore explores “the intersection, the confluence, and the common ground” among diverse epistemologies and worldviews, reflecting on how this space is to be harnessed in research, learning, and teaching (p. 112). She eloquently demonstrates how decolonization, or the Idea, is anything but a moment in time to be captured or missed.